2000
DOI: 10.1161/01.hyp.36.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Possible Locus on Chromosome 18q Influencing Postural Systolic Blood Pressure Changes

Abstract: Abstract-We conducted a genome-wide scan for quantitative trait loci influencing the systolic blood pressure, diastolic blood pressure, and pulse responses to a postural challenge in 498 white sibling-pairs from the Hypertension Genetic Epidemiology Network, a multicenter study of the genetic susceptibility to hypertension. All participants were hypertensive (systolic blood pressure Ն140 mm Hg, diastolic blood pressure Ն90 mm Hg, or on antihypertensive medications) with diagnosis before age 60. Blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 33 publications
1
57
2
Order By: Relevance
“…For example, some studies have found that DSBP to postural change (standing) is influenced by cigarette smoking, 3,5 certain antihypertensive medication 8,43 and BMI. 3,5,8 However, other studies indicate that BP response to postural change is not influenced by cigarette smoking, 8,13,43 hypertensive medication 3,5 or BMI. 4,13 It is possible that the covariate effects observed in some of these studies are influenced or obfuscated by multicollinearity among BP measures, and that the observed significant covariate effect may reflect an association with the portion of the variance of BP reactivity that is correlated with resting or general BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have found that DSBP to postural change (standing) is influenced by cigarette smoking, 3,5 certain antihypertensive medication 8,43 and BMI. 3,5,8 However, other studies indicate that BP response to postural change is not influenced by cigarette smoking, 8,13,43 hypertensive medication 3,5 or BMI. 4,13 It is possible that the covariate effects observed in some of these studies are influenced or obfuscated by multicollinearity among BP measures, and that the observed significant covariate effect may reflect an association with the portion of the variance of BP reactivity that is correlated with resting or general BP.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 One reason for these equivocal results is the fact that genetic factors are rarely accounted for in studies of BP reactivity. 11,12 A few studies have shown evidence for genes influencing BP changes in response to orthostasis (i.e., postural change), [13][14][15] but one aspect of this research that has been largely ignored is the identification of unique or shared genetic influences on different BP measures at rest and during orthostasis. In other words, do the same genes regulate BP both at rest and during orthostasis?…”
mentioning
confidence: 99%
“…The genetic influence on orthostatic BP dysregulation (OH or OHT) remains understudied. Previous familial studies indicate that genes responsible for orthostatic SBP disorder may be on chromosome 13q or 18q [33,34] . However, no exact candidate genes have been identified as being responsible for orthostatic SBP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Such polymorphisms may be subsequently genotyped in populations with genetic disorders that map to the chromosome, and used for further association studies in complex inheritance diseases such as bipolar disorder, and other disorders, including autosomal dominant orthostatic hypotensive disorder, 28 a locus for postural systolic blood pressure response, 29 IDDM6, 30 Grave's disease, 31 Paget disease of bone, 32 and dyslexia 33 that have been mapped on this chromosome.…”
Section: Resultsmentioning
confidence: 99%